1993
DOI: 10.1088/0029-5515/33/3/i04
|View full text |Cite
|
Sign up to set email alerts
|

Time resolved energy spectrum of the axial ion beam generated in plasma focus discharges

Abstract: The energy spectrum of the deuteron beam along the electrode axis (0 degrees ) in a plasma focus discharge has been determined with a time of flight (TOF) method and with a differential filter method in the ion energy interval E=0.3-9 MeV. The ion TOF method is applied to single-ion pulse events with an ion emission time t(E) that is only weakly dependent on the ion energy E for E>0.3 MeV. The correlation of the ion beam intensity with the filling pressure, the neutron yield and the hard X-ray intensity is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 7 publications
3
41
0
Order By: Relevance
“…The ion beam energy is comparable to that measured in similar size devices with slower rise-times [2]. The ion beam energy measured along the z-axis increases linearly with neutron yield.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…The ion beam energy is comparable to that measured in similar size devices with slower rise-times [2]. The ion beam energy measured along the z-axis increases linearly with neutron yield.…”
Section: Discussionsupporting
confidence: 63%
“…Multiple experiments [1,2] report measured deuteron energies >5 MeV on DPFs, including a machine with as little as 5.4 kJ stored energy. Neutrons are produced when the device is operated with deuterium or tritium gas.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[35][36][37] However, the lowest and the highest energy ions may differ from the experiment to experiment and the detection methodology. Bostick et al observed the deuteron energy spectrum ranging from 300 keV to 9 MeV, 38 whereas Gardin et al measured the deuteron energy down to around 25 keV. 39 While studying the characteristics of the hydrogen ion beam, Takao et al observed that the energy spectrum of the proton is distributed from a value in between 150 keV and 2 MeV.…”
Section: -3mentioning
confidence: 99%